Reference range of neutrophil-to-lymphocyte ratio in healthy individuals and its predictive value for post-trauma nosocomial infections - Wang, Qiang; Jiang, Yu; Jin, Feifei; Gan, Lebin; Li, Rui; Sun, Diya; Zhang, Mengwei; Pei, Zishuo; Zhang, Jingyao; Ye, Jingjing; Wang, Tianbing (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThis study aimed to establish the reference range of the neutrophil-to-lymphocyte absolute ratio (NLR) in healthy individuals, explore the association between NLR and post-trauma nosocomial infections, and evaluate the effectiveness of NLR in predicting clinical outcomes of post-trauma infections.MethodsA retrospective analysis was conducted based on medical records of acute trauma patients from the China National Center for Trauma Medical and health examination data from Chengdu First People’s Hospital, Sichuan Province. The reference range of NLR was established, and multivariate logistic regression analysis was performed to identify risk factors for infection, with subgroup analysis conducted by age. The predictive value of NLR for post-trauma infections was assessed using the area under the receiver operating characteristic curve (AUC).ResultsA total of 175,019 individuals were included, comprising 165,504 healthy individuals (753 minors [0.45%, <18 years] and 164,751 adults [99.55%]) and 9,515 acute trauma patients (8,602 in the control group [90.40%] and 913 with post-trauma infections [9.60%]). The 2.5th-97.5th percentile range for NLR was 0.69-3.48 in minors and 0.86-3.83 in adults. NLR was identified as an independent risk factor for post-trauma infections, with an odds ratio (OR) of 1.43 (95% CI: 1.18-1.73). Additionally, NLR showed a positive correlation with common inflammatory markers, CRP (r = 0.37 [0.32-0.42], weak correlation) and PCT (r = 0.52 [0.45-0.58], moderate correlation). Receiver operating characteristic (ROC) analysis demonstrated that NLR had an AUC of 0.71 (95% CI: 0.69-0.73, P < 0.0001) for predicting infections, with a diagnostic cutoff value of 4, sensitivity of 60.28% (95% CI: 59.24-61.31), and specificity of 72.85% (95% CI: 69.71-75.77). No significant differences in NLR values were observed between groups with pulmonary infections, urinary tract infections, combined pulmonary and urinary infections, and soft tissue infections (P > 0.05). However, NLR values were significantly higher in patients with fungal infections compared to those without (P = 0.03).ConclusionThe current 2.5th-97.5th percentile range of NLR is 0.69-3.48 in minors and 0.86-3.83 in adults. With increasing age, the reference range widens, and females tend to have a slightly broader range than males. NLR is an independent risk factor for post-trauma infections, showing higher predictive value in patients over 60 years of age. Although NLR cannot differentiate infection sites or pathogen types, elevated NLR values may provide a reference for identifying fungal infections.